Interface roughness induced intrasubband scattering in a quantum well under an electric field - Ibragimov, G.B. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2002)
Scattering rates in the lowest subband in a quantum well are calculated for interface roughness scattering when an electric field is applied normally to the layer plane. It is found that the interface roughness scattering rate increases with increasing electric field. The electric field changes the interface roughness scattering rates drastically in thick QWs as compared with those for the zero-field case.